If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -7 + 9 + -2 = x + 2 Reorder the terms: -7 + 9 + -2 + 3x = x + 2 Combine like terms: -7 + 9 = 2 2 + -2 + 3x = x + 2 Combine like terms: 2 + -2 = 0 0 + 3x = x + 2 3x = x + 2 Reorder the terms: 3x = 2 + x Solving 3x = 2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3x + -1x = 2 + x + -1x Combine like terms: 3x + -1x = 2x 2x = 2 + x + -1x Combine like terms: x + -1x = 0 2x = 2 + 0 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 4b-3a=8b | | Y^2-225= | | 5x+22=7x+32 | | 12x-24=4x+8 | | (x*.0625)+(x*.2)+x=30 | | 15-4y=51 | | 9(x+4)-7=37-2x-8+11x | | 4/7x-1/30=-3/7x-1/5 | | p/2-p/4 | | 5x-6=-x | | 3x-2(5-3x)=8 | | 4+5x-10=-x | | 9a+16=2n+33 | | (3u^8u^-12w^9/u^2w^5)^-2 | | IXI=5/9 | | 2x-15=1-2x | | 2p-9=10p-49 | | 25+(-10)= | | 6(z+1)=5z | | -9(z+8)=-9z-7 | | 13x+16=42 | | 2a+b=0.125 | | 18x^3/2x | | 6x/5*3y/7 | | 21x+16-8x=42 | | 7/8x3/4= | | 8z+1-z=6+6z+6 | | 4*x=x | | Y=x^3+c^2-12x | | hbt=2(3.14) | | 0.75x=92 | | 3y=19x+86 |